High Temperature Study of Industrial Slag from Further Modelling Point of View - Ślęzak, M.; Karbowniczek, M.; Migas, P.; Ślęzak, W. (Archives of Metallurgy and Materials, 2021)
This paper deals with the subject of high temperature analysis of refining slags originating from a ladle from an actual/industrial secondary refining process. The objective of the conducted research was to learn about the rheological behaviour of the complex industrial slag systems analysed in conditions of variable rheological parameters and temperature, also analyses with a high-temperature microscope. The analysed system seems to be a Newtonian body (with viscosity between 0.1 and 0.8 Pa·s, depend on temperature value, and chemical composition).
Keywords: viscosity; slag; steelmaking modelling